Everolimus Alleviates Renal Allograft Interstitial Fibrosis by Inhibiting Epithelial-to-Mesenchymal Transition Not Only via Inducing Autophagy but Also via Stabilizing IκB-α - Gui, Zeping; Suo, Chuanjian; Tao, Jun; Wang, Zijie; Zheng, Ming; Fei, Shuang; Chen, Hao; Sun, Li; Han, Zhijian; Ju, Xiaobing; Zhang, Hengcheng; Gu, Min; et al. (Frontiers in Immunology, 2022)
Chronic allograft dysfunction (CAD) is the major cause of late graft loss in long-term renal transplantation. In our previous study, we found Epithelial–mesenchymal transition (EMT) is a significant event in the progression of renal allograft tubulointerstitial fibrosis, and impaired autophagic flux plays a critical role in renal allograft fibrosis. Everolimus (EVR) has been reported to widely used to prevent the progression of organs fibrosis and graft rejection. However, the pharmacological mechanism of EVR in kidney transplantation remains to be determined. We used CAD rat model and human kidney 2 (HK2) cells line treated with tumor necrosis factor-α (TNF-α) and EVR to examine the role of EVR on TNF-α-induced-EMT and transplanted renal interstitial fibrosis. Here, we found that EVR could attenuate the progression of EMT and renal allograft interstitial fibrosis, and also activate autophagy in vivo. To explore the mechanism behind it, we detected the relationship among EVR, autophagy level and TNF-α-induced-EMT in HK2 cells. Our results showed that autophagy was upregulated upon mTOR pathway inhibition by EVR which could significant reduced expression of TNF-α-induced-EMT. However, the inhibition of EVR on TNF-α-induced-EMT was partly reversed following the addition of autophagy inhibitor chloroquine. In addition, we found that TNF-α activated EMT through protein kinase B (Akt) as well as nuclear factor kappa B (NF-κB) pathway according to the RNA sequencing, and EVR’s effect on the EMT was only associated with IκB-α stabilization instead of Akt pathway. Together, our findings suggest that EVR may retard impaired autophagic flux and block NF-κB pathway activation, thereby prevent progression of TNF-α-induced-EMT and renal allograft interstitial fibrosis.